Search for new particles in two-jet final states in 7 TeV proton-proton collisions with the ATLAS detector at the LHC - Aad, Georges; Andrei, George Victor; Dietzsch, Thorsten; Hanke, Paul; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; Männer, Reinhard; Meier, Karlheinz; Müller, Felix; Poddar, Sahill; Radescu, Voica; et al. (Physical review letters, 2010)
A search for new heavy particles manifested as resonances in two-jet final states is presented. The data were produced in 7 TeV proton-proton collisions by the LHC and correspond to an integrated luminosity of 315 nb−1 collected by the ATLAS detector. No resonances were observed. Upper limits were set on the product of cross section and signal acceptance for excited-quark (q∗) production as a function of q∗ mass. These exclude at the 95% C.L. the q∗ mass interval 0.30<mq∗<1.26 TeV, extending the reach of previous experiments.